Litter quality and decomposition in a CO2-enriched Mediterranean forest ecosystem - Angelis, Paolo De (Plant and Soil, 2000)
Six large open top chambers were installed to test the effect of atmospheric [CO2] enrichment on clumps of natural Mediterranean vegetation starting from early spring 1992. To study the impact of [CO2] enrichment on litter decomposition, leaves of three woody species (Quercus ilex L., Phillyrea angustifolia L. and Pistacia lentiscus L.) were collected from the forest ﬂoor and subsequently incubated in situ over a two-year period. The initial slope of the exponential function, describing mass loss, indicated that there was a small negative effect of elevated [CO2] on the decomposition rate of all the species. All regressions were signiﬁcant. The decrease of decomposition rate is particularly notable during the initial stages of decomposition, when the differences of quality parameters, lignin/N and C/N were larger. This study points out that a decrease of decomposition rate may occur under elevated [CO2] conditions; if this effect is coupled to an increase of primary production, there will be a net rise of C-storage in the soils of forest ecosystems. Forest soils may, therefore, represent a potentially increasing sink for this excess carbon.
Keywords: decomposition rates; elevated [CO2]; litter quality; mediterranean forest; Quercus ilex

Litter quality and decomposition in a CO2-enriched Mediterranean forest ecosystem - Angelis, Paolo De (Plant and Soil, 2000)
Six large open top chambers were installed to test the effect of atmospheric [CO2] enrichment on clumps of natural Mediterranean vegetation starting from early spring 1992. To study the impact of [CO2] enrichment on litter decomposition, leaves of three woody species (Quercus ilex L., Phillyrea angustifolia L. and Pistacia lentiscus L.) were collected from the forest ﬂoor and subsequently incubated in situ over a two-year period. The initial slope of the exponential function, describing mass loss, indicated that there was a small negative effect of elevated [CO2] on the decomposition rate of all the species. All regressions were signiﬁcant. The decrease of decomposition rate is particularly notable during the initial stages of decomposition, when the differences of quality parameters, lignin/N and C/N were larger. This study points out that a decrease of decomposition rate may occur under elevated [CO2] conditions; if this effect is coupled to an increase of primary production, there will be a net rise of C-storage in the soils of forest ecosystems. Forest soils may, therefore, represent a potentially increasing sink for this excess carbon.
Keywords: decomposition rates; elevated [CO2]; litter quality; mediterranean forest; Quercus ilex

Responses to elevated atmospheric CO2 concentration and nitrogen supply of Quercus ilex L. seedlings from a coppice stand growing at a natural CO2 spring - Tognetti, Roberto; Johnson D., Jon (Ann. For. Sci., 1999)
Quercus ilex acorns were collected from a population of trees with a lifetime exposure to elevated atmospheric CO2 concentration (CO2), and after germination seedlings were exposed at two [CO2] (370 or 520 μmol mol-1) in combination with two soil N treatments (20 and 90 μmol mol -1 total N) in open-top chambers for 6 months. Increasing [CO2 ] stimulated photosynthesis and leaf dark respiration regardless of N treatment. The increase in photosynthesis and leaf dark respiration was associated with a moderate reduction in stomatal conductance, resulting in enhanced instantaneous transpiration efficiency in leaves of seedlings in CO2 enriched air. Elevated [CO2] increased biomass production only in the high-N treatment. Fine root/foliage mass ratio decreased with high-N treatment and increased with CO2 enrichment. There was evidence of a preferential shift of biomass to below-ground tissue at a low level of nutrient addition. Specific leaf area (SLA) and leaf area ratio (LAR) decreased significantly in leaves of seedlings grown in elevated [CO2] irrespective of N treatment. Leaf N concentration decreased significantly in elevated [CO2] irrespective of N treatment. As a result of patterns of N and carbon concentrations, C/N ratio generally increased with elevated [CO2] treatment and decreased with high nutrient supply. Afternoon starch concentrations in leaves did not increase significantly with increasing [CO2], as was the case for morning starch concentrations at low-N supply. Starch concentrations in leaves, stem and roots increased with elevated [CO2] and decreased with nutrient addition. The concentration of sugars was not significantly affected by either CO 2 or N treatments. Total foliar phenolic concentrations decreased in seedlings grown in elevated [CO 2] irrespective of N treatment, while nutrient supply had less of an effect. We conclude that available soil N will be a major controlling resource for the establishment and growth of Q. ilex in rising [CO 2] conditions
Keywords: carbon physiology; elevated [CO2]; natural CO2 springs; nitrogen; Quercus ilex

Long-term exposure to elevated in a natural Quercus ilex L. community: net photosynthesis and photochemical efficiency of PSII at different levels of water stress - Scarascia-Mugnozza, G (Plant, Cell & Environment, 1996)
Naturally grown trees of Mediterranean evergreen oak (Quercus ilex L.), representing tbe climax species of tbe region, were enclosed in six large open-top chambers and exposed to ambient and elevated CO2 concentrations during a 3 year period. Maximum daily net photosynthetic rates measured at the two different CO2 concentrations were from 30 to 100% higher in elevated than in ambient [CO2] throughout the experimental period. The increase in maximum daily photosynthesis was also accompanied by a 93% rise in the apparent quantum yield of CO2 assimilation, measured during periods of optimum soil moisture conditions. Hence, no clear evidence of downregulation of net photosynthetic activity was found. Interactions between atmospheric CO2 concentration and plant water stress were studied by following the natural evolution of drought in different seasons and years. At each level of water stress, the maximum rate of carbon assimilation was higher in elevated than in ambient [CO2I by up to 100%. Analysis of in vivo chlorophyll fluorescence parameters in normal (21%) and low (2%) oxygen concentrations provided useful insights into the functioning and stability of the photosynthetic processes. The photochemical efficiency of PSII (Fy/F„,) progressively decreased as drought conditions became more evident; this trend was accentuated under elevated tCO2]. Thermal de-excitation processes were possibly more significant under elevated than Under ambient [CO2], in a combination of environmental stresses. This research suggests two possible conclusions: (i) a 'positive' interaction between elevated [CO2] and carbon metabolism can be obtained through relief of water stress limitation in the summer months, and (ii) elevated [CO2], under drought conditions, may also enhance the significance of slow-relaxing quenching.
Keywords: chlotophyll fluorescenee; elevated [CO2]; Mediterranean ecosystems; photosynthesis; Quercus ilex L.; water stress